Developing a Word Composition Educational Game for Young Children After the Covid-19 Pandemic - Iskandar, Akbar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
The purpose of this study is to develop a word composition educational game for young children in the post-COVID-19 pandemic era. The game is designed to help children strengthen their word composition skills and introduce new letters and syllables related to fruits. Utilizing a 2D display, the game was developed using the Construct 2 game engine and followed the waterfall development method. The game's effectiveness was validated through testing with 10 parents and teachers, demonstrating its potential in aiding children's learning of word composition. The study results indicate that the integration of gamification and technology in early childhood education significantly enhances children's motivation and learning outcomes. The use of Construct 2 enabled the creation of a user-friendly and visually appealing educational game. This study contributes to knowledge by providing an innovative approach to improving children's word composition skills in an engaging manner. Additionally, it highlights the broader potential of gamified learning tools to transform traditional educational practices, offering valuable insights for future educational technology development.